Глобальні мегатренди людства, четверта промислова революція та напрямки розвитку майбутньої економіки. Великі дані - Григоров, Отто Володимирович; Аніщенко, Галина Оттівна; Стрижак, Всеволод Вікторович; Петренко, Надія Олександрівна; Турчин, Ольга Володимирівна; Окунь, Антон Олександрович (Український державний університет залізничного транспорту, 2019)
У статті розглянуто основні ознаки Великих даних, галузь їх застосування, зв'язок із машинним навчанням. Наведені інструменти для роботи з Великими даними, приклади можливостей таргетованої реклами на основі їх аналізу. Оцінено перспективи та труднощі використання принципів Big Data на базі прикладів застосування у транспортних системах, логістичних комплексах, ліфтобудуванні й медицині.

The article deals with the main features of Big Data, the area of their application, the connection with machine learning. It is described that a self-studying program receives an arbitrary set of data units that conform to a certain pattern and after studying this set, the program is a model of this pattern, that is, a set of criteria by which the algorithm can determine whether a specific unit of data is the desired pattern or not. In the future, applying this model to a new and random data set, the program can find in it the units of data in which the pattern is executed. Professional tools for working with Big Data, such as software products and distributed computing (cloud computing) are considered. The means for working with Big Data, examples of targeted advertising based on their analysis are described. The effectiveness of targeted advertising application based on the use of analysis of character traits using the most popular personality model "Big Five" known also as OCEAN (openness to experience, conscientiousness, extraversion, agreeableness, neuroticism), surface characteristics and human way of life are estimated. The effectiveness of personalized advertising on the basis of the results of psychometric analysis using Big Data on an example of an election campaign is investigated. It is shown how the electorate's research was conducted, through simulation, division into different segments, with each of them being actively interacted with ethereal and targeted television advertising, as well as through advertising on the Internet. An estimation of perspectives and difficulties of using Big Data principles on the basis of application examples in various transport systems, resource savings, logistic complexes and systems, elevator building and medical industry.
Global megatrends of humanity, fourth industrial revolution and developments of the future economy. Big data
Keywords: транспортні технології; Індустрія 4.0; таргетована реклама; логістичні системи; транспортні системи; transport technologies; Industry 4.0; targeted advertising; logistic systems; transport systems